Increased long chain acyl-Coa synthetase activity and fatty acid import is linked to membrane synthesis for development of picornavirus replication organelles. - Jules A Nchoutmboube; Ekaterina G Viktorova; Alison J Scott; Lauren A Ford; Zhengtong Pei; Paul A Watkins; Robert K Ernst; George A Belov (PLoS Pathogens, 2013)
All positive strand (+RNA) viruses of eukaryotes replicate their genomes in association with membranes. The mechanisms of membrane remodeling in infected cells represent attractive targets for designing future therapeutics, but our understanding of this process is very limited. Elements of autophagy and/or the secretory pathway were proposed to be hijacked for building of picornavirus replication organelles. However, even closely related viruses differ significantly in their requirements for components of these pathways. We demonstrate here that infection with diverse picornaviruses rapidly activates import of long chain fatty acids. While in non-infected cells the imported fatty acids are channeled to lipid droplets, in infected cells the synthesis of neutral lipids is shut down and the fatty acids are utilized in highly up-regulated phosphatidylcholine synthesis. Thus the replication organelles are likely built from de novo synthesized membrane material, rather than from the remodeled pre-existing membranes. We show that activation of fatty acid import is linked to the up-regulation of cellular long chain acyl-CoA synthetase activity and identify the long chain acyl-CoA syntheatse3 (Acsl3) as a novel host factor required for polio replication. Poliovirus protein 2A is required to trigger the activation of import of fatty acids independent of its protease activity. Shift in fatty acid import preferences by infected cells results in synthesis of phosphatidylcholines different from those in uninfected cells, arguing that the viral replication organelles possess unique properties compared to the pre-existing membranes. Our data show how poliovirus can change the overall cellular membrane homeostasis by targeting one critical process. They explain earlier observations of increased phospholipid synthesis in infected cells and suggest a simple model of the structural development of the membranous scaffold of replication complexes of picorna-like viruses, that may be relevant for other (+)RNA viruses as well.